Europe and money - Coffey, Peter (London : Macmillan, 1977)
The book examines evolving national principles of economic and monetary policy. It also considered the theory of economic integration and its relevance to the European Economic Community as well as the future of Europe and money policies.
Includes bibliographical references and index.
usc 19/09/18
Loans
Keywords: Monetary policy; Monetary unions; International economic integration; Europe--European Economic Community countries